Subduing the Hepatotoxic and Urotoxic Effects of Cyclophosphamide using Natural Antioxidants - S. Iyer, Sudarshan; Mishra, Sabyasachi; Ohdar, Khushboo; Subramanian*, Senthilkumar (Asian Journal of Chemistry, 2014)
Cyclophosphamide is a commercially popular chemotherapeutic drug and is used in the treatment of malignant and non-malignant forms of cancer. Action of hepatic microsomal enzymes on cyclophosphamide metabolizes it into phosphoramide mustard and acrolein. These are toxic and are majorly found to have adverse effects on the kidney and liver causing symptoms like dypsia, fibrosis, hemorrhagic cystitis and necropsis. Acrolein-one of the metabolites was found to interact with majority of biomolecules like DNA, RNA and proteins that may lead to cellular apoptosis. Cyclophosphamide metabolism was also known to induce the production of reactive oxygen species leading to total cellular damage, which causes various acute and chronic diseases. Herbal plants are found to be rich in antioxidant and have anticancerous and tumor reducing properties. Present study aimed in achieving modulatory action of the poly-herbal combination BC and vitamin E on cyclophosphamide induced hepato- and uro-toxicity. Wistar rats (male and female) were treated orally with the 100 mg/kg of the BC and 50 mg/kg of Vit-E for whole of the study (30 days). 200 mg/kg of cyclophosphamide was administered in 2 split doses through i.p. on day 20 and 21. Serum was used to analyze the clinical chemistry parameters such as total protein, albumin, bilirubin (total and direct), urea, creatinine and enzymes like AST and ALT. Parameters that were significantly altered due to cyclophosphamide administration were modulated during treatment using BC + Vit-E (BCE). By these preliminary studies, it has been hypothesized that the effects of cyclophosphamide were treated to a great extent and therapeutic effect of cyclophosphamide has been sensitized by BCE.